Evaluation Of Arabic Learning Using The Kahoot Application In The Pandemic Era Of Covid-19 - Mira Mira; Syihabudin Syihabudin; Yayan Nurbayan (Fakultas Tarbiyah dan Keguruan UIN Sunan Gunung Djati Bandung, 2020)
This study aims to measure the extent of the benefits of technological development as a means of academic evaluation. On this occasion, the researcher chose the Kahoot program as a model, a game-based smartphone learning program used as a school and educational stream designed by two scientists from the University of Norway. Researchers use the program of using the Kahoot program in the implementation process for students participating in Arabic language training courses at the Language Center of the State Islamic University of Sunan Gunung Djati Bandung, the results of the study show that this program is of great use to teachers when they show tables that are more effective and efficient, because of the program. It is easy to use question setting by teachersand teachers. It is reliable and can predict the results of decisions after students have answered questions. Apart from that, this program also provides students with fun games such as game programs and can also be accessed easily via smartphones. Researchers hope that this study's results can provide additional information and input for teachers to increase the use of technology in the online teaching and learning process, especially during the Covid-19 epidemic, so that the teaching and learning process is more exciting effective.